Interaction of age and attention on driving performance - Motamedi, Mona; Slawinski, Elzbieta B. (Canadian Acoustics, 2003)
A study was conducted on the effects of age and attention levels to auditory distracters on ability to detect external vehicular warning signals. Results showed that the level of attenuation to a warning signla decreased when participants were attending to the distracter and simultaneously to the warning signlas. Thus, the effect of age was manifested in a decrease in the level of attenuation for both the attended and unattended conditions obtained for elderly participants.